Dampak Dikeluarkannya Edik Milano 313 bagi Kebebasan Gereja - Jon Mister R. Damanik (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2021)
Church history is not an outdated or outdated writing, but church history has an important role to play. Because in the history of the church there are important parts that can be used as a teaching for the church today. Chrestus is a term for followers of Christ, and Christians are used as an outlet for pleasure when they are persecuted, pitted against hungry animals, used as torches to light the garden, nearly 250 years of persecuted Christians have not been given freedom by the state even if there is a problem -problems like a fire whose cause is Christians because they do not worship their gods so that the gods are angry. The Edik Milan is a decree issued in 313 which greatly influenced the church's freedom to carry out religious activities. The meaning of Edik is: